Exit Dynamics with Rational Expectations - Arvid Raknerud; Rolf Golombek (Statistics Norway, Research Department, 2000)
We develop an econometric model for firm exit, using stochastic dynamic programming (SDP) as a starting point. According to SDP, the value of an operating firm can be written as the sum of (i) the net present value of continuing production if the firm is committed to a future exit date, and (ii) the value of the exit option. By approximating the option value by a simple function of its determinants, we derive an expression for the distribution of firm exit probabilities. The model is estimated by pseudo likelihood methods using panel data from the Norwegian Manufacturing Statistics. The applicability of the model is illustrated by assessing to what extent quotas on emissions of carbondioxide increase exits in manufacturing sectors.
Keywords: C33; C51; C61; D21; Q38; 330; Exit dynamics; stochastic dynamic programming; option value; pseudo likelihood; dynamic panel data; random effects; environmental taxes